From suffering to resignation: Grounded Theory approach to maternal experience with newborn in phototherapy - Nascimento, Tayomara Ferreira; Avila, Marla Andréia Garcia De; Bocchi, Silvia Cristina Mangini (Instituto de Medicina Integral Prof. Fernando Figueira, 2018)
AbstractObjectives: understanding the experience of puerperal womenwith newborn in phototherapy treatment in rooming-in care.Methods: qualitative research analyzed according to the Grounded Theory and the results discussed in the light of Symbolic Interactionism. The interviews were audiotaped and transcribed in full. The theoretical saturation was based on the analysis of the 15th interview with puerperal women, undergoing the experience in the maternity of the Public Hospital of São Paulo State.Results: from the analysis emerged four categories (sub processes): getting disappointed with the bad news; feeling recluse, separated from her baby, accountable and with not enough support for care; resigning to the protective role of mother of a baby in suffering and at risk; seeking strategies to deal with the situation. From the realignment of these categories (sub processes) emerged the core category (process): from suffering to resignation in order to deal with the maternal experience with NB in phototherapy.Conclusions: the symbolic intervening component, mother's protective role, prompted her to attempt to cope with the challenging experience by feeling compelled to exercise the function of caretaker. The same way that the rooming-in care team emerged in the experience of the mother, using the same symbol, to hold her accountable for constant vigilance in maintaining the integrity of baby's vision.

ResumoObjetivos: compreender a experiência de puérperas com recém-nascido em tratamento fototerápico em alojamento conjunto.Métodos: pesquisa qualitativa analisada segundo a Teoria Fundamentada nos Dados e os resultados discutidos à luz do Interacionismo Simbólico. As entrevistas foram audio-gravadas e transcritas na íntegra. A saturação teórica deu-se a partir da análise da 15ª entrevista com puérperas, vivenciando a experiência em maternidade de Hospital Público do Estado de São Paulo.Resultados: da análise emergiram quatro categorias (subprocessos): decepcionando-se com a má notícia; sentindo-se reclusa, apartada do bebê, responsabilizada e com apoio insuficiente para o cuidado; resignando-se ao papel protetor de mãe de bebê em sofrimento e em risco; buscando estratégias para lidar com a situação. Do realinhamento dessas categorias (subprocessos) emergiu a categoria central (processo): do sofrimento à resignação para enfrentar a experiência materna com recém-nascido em fototerapia.Conclusões: o componente interveniente simbólico, papel protetor de mãe, impulsionou-a a tentativas de lidar com a experiência desafiante ao se sentir compelida ao exercício de cuidadora. Da mesma forma que, a equipe do alojamento conjunto emergiu na vivência dessa mãe, utilizando-se do mesmo símbolo, para responsabilizá-la pela vigilância constante na manutenção da integridade da visão do bebê.
Do sofrimento à resignação: experiência materna com recém-nascido em fototerapia na abordagem Grounded Theory
Keywords: Jaundice neonatal; Phototherapy; Rooming-in care; Maternal and child health; Qualitative research; Icterícia neonatal; Fototerapia; Alojamento conjunto; Saúde materno-infantil; Pesquisa qualitativa